AUTHENTIC MATERIALS AS A MEANS OF DEVELOPING READING SKILLS IN TEACHING A FOREIGN LANGUAGE: SELECTION CRITERIA AND BENEFITS (American Journal of Interdisciplinary Research and Development, 2023)
This article proposes a methodology for using authentic materials in teaching students a foreign language. The main criteria for selecting authentic materials in accordance with the purpose and objectives of training are identified, and the advantages of their use for developing reading skills in comparison with adapted texts and increasing the level of motivation for learning a foreign language are analyzed.